On the semi-sub-hypergroups of a hypergroup - Ch. G. Massouros (International Journal of Mathematics and Mathematical Sciences, 1991)
In this paper we study some properties of the semi-sub-hypergroups and the closed sub-hypergroups of the hypergroups. We introduce the correlated elements and the fundamental elements and we connect the concept antipodal of the latter with Frattin's hypergroup. We also present Helly's Theorem as a corollary of a more general Theorem.